Hepcidin-to-Ferritin Ratio Is Decreased in Astrocytes With Extracellular Alpha-Synuclein and Iron Exposure - Cui, Juntao; Guo, Xinli; Li, Qijun; Song, Ning; Xie, Junxia (Frontiers in Cellular Neuroscience, 2020)
Astrocytes are the most abundant glial cells in the central nervous system. As indispensable element of the neurovascular unit, astrocytes were involved in the inflammatory response and disease-related processes. In the extracellular space, alpha-synuclein (α-syn) released by neurons, and adjacent astrocytes can internalize the transmitted α-syn, the latter activating glial cells to induce neuroinflammation. We are interested in whether astrocytes-mediated neuroinflammation was modulated by intracellular status iron and extracellular α-syn. The results showed that recombinant α-syn (1 μg/ml and 5 μg/ml) treatment for 24 h did not affect the expression of iron transporters divalent metal transporter 1 (DMT1) and ferroportin 1 (FPN1), as well as iron regulatory protein (IRP) 1 and IRP2. Several proinflammatory cytokines, e.g. tumor necrosis factor-α (TNF-α), interleukin (IL) 1β and IL-6 were up-regulated on mRNA levels in 5 μg/ml α-syn treated astrocytes, together with an increased release of TNF-α, indicating the inflammatory responses were triggered in these cells. Pretreatments of iron-overload reagent ferric ammonium citrate (FAC, 100 μmol/L) for 24h have no effects on the mRNA levels and release of these proinflammatory cytokines, also have no effects on α-syn triggered responses. Iron chelator desferrioxamine (DFO, 100 μmol/L) exerted suppressive effects on TNF-α mRNA levels, although no change was observed on TNF-α release. Hepcidin mRNA levels was down-regulated significantly in astrocytes co-treated with FAC and α-syn, although neither FAC or α-syn could regulate hepcidin levels separately. On the contrary, hepcidin mRNA levels was up-regulated in DFO/α-syn treated cells, in parallel with an increase IL-6 mRNA levels. As expected, ferritin protein levels were up-regulated or down-regulated with FAC or DFO treatment. Upon the up-regulation of ferritin exerted by α-syn, hepcidin to ferritin levels was more indicative for the modulatory effects in α-syn-treated astrocytes with altered iron status. Therefore, we proposed hepcidin to ferritin ratio was more indicative as a detrimental response in primary cultured astrocytes experiencing iron and extracellular α-syn.